2013
DOI: 10.1371/journal.pgen.1003894
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide High-Resolution Mapping of UV-Induced Mitotic Recombination Events in Saccharomyces cerevisiae

Abstract: In the yeast Saccharomyces cerevisiae and most other eukaryotes, mitotic recombination is important for the repair of double-stranded DNA breaks (DSBs). Mitotic recombination between homologous chromosomes can result in loss of heterozygosity (LOH). In this study, LOH events induced by ultraviolet (UV) light are mapped throughout the genome to a resolution of about 1 kb using single-nucleotide polymorphism (SNP) microarrays. UV doses that have little effect on the viability of diploid cells stimulate crossover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
106
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(128 citation statements)
references
References 58 publications
(110 reference statements)
20
106
2
Order By: Relevance
“…In this depiction, red and blue lines represent levels of hybridization to W303-1A-and YJM789-derived SNPs, respectively. An interstitial LOH event is shown in Figure 1A; from previous studies Yin and Petes 2013), we know that these events reflect gene conversion, the nonreciprocal transfer of sequences from one homolog to the other. In this example, sequences of the YJM789 copy of chromosome II were copied into the W303-1A copy of chromosome II at two different locations.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…In this depiction, red and blue lines represent levels of hybridization to W303-1A-and YJM789-derived SNPs, respectively. An interstitial LOH event is shown in Figure 1A; from previous studies Yin and Petes 2013), we know that these events reflect gene conversion, the nonreciprocal transfer of sequences from one homolog to the other. In this example, sequences of the YJM789 copy of chromosome II were copied into the W303-1A copy of chromosome II at two different locations.…”
Section: Resultsmentioning
confidence: 87%
“…The transition between heterozygous and homozygous SNPs should contain the site of the recombination-initiating lesion Yin and Petes 2013). Breakpoint regions in subcultured mutant strains were examined to determine if specific chromosome elements (for example, autonomously replicating sequence, ARS elements) were overrepresented at the breakpoints.…”
Section: Association Of Genome Features With Recombination Eventsmentioning
confidence: 99%
“…Since mitotic crossover can result in LOH throughout the region centromere-distal to the crossover, which can be detrimental, it seems logical that noncrossover repair pathways would predominate. This hypothesis has been supported by several studies that found crossover-associated conversions to be approximately one-quarter to one-third of all conversions (Haber and Hearn 1985;Chua and Jinks-Robertson 1991;Inbar and Kupiec 1999;Nickoloff et al 1999;Yin and Petes 2013), but three studies reported that half or nearly half of all conversions were crossover-associated (Aguilera and Klein 1989;Welz-Voegele and Jinks-Robertson 2008;Yim et al 2014). In this study, among the 79 gene conversions collected from cells grown under replication stress (no galactose), 30% were crossover-associated and 70% were noncrossoverassociated.…”
mentioning
confidence: 76%
“…In most previous studies, the mechanics of the assay system limited the extent of the geneconversion event to 2 kb or less. It is not clear, therefore, whether long conversion tracts observed in our study are generated solely through this mechanism or may involve alternative pathways, such as repair of a double-stranded DNA gap or an interstitial BIR event that switches templates (23).…”
Section: Analysis Of Conversion Tracts Associated With Reciprocal Cromentioning
confidence: 91%
“…The experiments described above did not allow us to distinguish cross-overs and BIR events, nor to examine the types of gene conversions associated with cross-overs. For this analysis, we used diploid strains in which cross-overs could be detected by a sectoring assay (22,23,26). In these strains, one homolog has the ochre-suppressor SUP4-o located near the telomere and the hygromycin-resistant HYG gene located at a similar position on the other homolog; in addition, the diploid is homozygous for ade2-1, an ochre mutation that, when unsuppressed, results in red colonies.…”
Section: Experimental Approach For Mapping Regions Of Loss Of Heterozmentioning
confidence: 99%